The Strategy of the Principal in Improving the Quality of Institutional Education - Ali Muhdlorul Huda; Mauhibur Rokhman (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This article aims to describe and analyze the planning, implementation, and evaluation of Madrasahs in strengthening the quality of education at MI (Islamic Elementary School) Miftahul Ulum, Kesambenwetan Village, Driyorejo District. This article uses a qualitative research type with a case study design, taking the research location at MI Miftahul Ulum. Methods of data collection are done by (1) interview (2) observation (3) documentation. Data analysis used the Miles and Huberman model: namely data reduction, data presentation, and conclusion drawing. The research findings show that: 1) Madrasah planning in improving the quality of education at MI Miftahul Ulum through a) Internal environmental analysis b) External environment analysis c) strategy selection, 2) Madrasah implementation in improving the quality of basic education, through, a) Tahfidz class programs, b) superior class program c) Extracurricular program The conclusion obtained is that improving the quality of education begins with the commitment of Madrasahs in improving the quality of education, followed by increasing the resources of teachers and education personnel, and principal management and implementation of strategies to improve quality. The quality applied is, though, a) Tahfidz class program, b) superior class program c) Extracurricular program.